2020
DOI: 10.2147/ndt.s241780
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Determinants of Long-Term Utilization of Antidepressant Drugs: A Retrospective Cohort Study</p>

Abstract: Purpose: Antidepressant consumption has risen in recent years, driven by longer treatment duration. The objective of this study was to measure the prevalence of antidepressant longterm and chronic use in the Bologna area, Italy, and to identify their main determinants. Materials and Methods: We conducted a retrospective claims-based cohort study by using the Bologna Local Health Authority data. A cohort of 18,307 incident users of antidepressant drugs in 2013 was selected, and subjects were followed for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
(110 reference statements)
0
12
0
Order By: Relevance
“… 31 Among them, 10% used more than 180 defined daily doses (DDDs) per year. 31 In addition to these significant changes in prescriptions and use over time, the prevalence in antidepressant drug use also varies according to age, 12 14 sex, 12 country 14 25 32 33 and antidepressant agent or class. 17 32 34 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 Among them, 10% used more than 180 defined daily doses (DDDs) per year. 31 In addition to these significant changes in prescriptions and use over time, the prevalence in antidepressant drug use also varies according to age, 12 14 sex, 12 country 14 25 32 33 and antidepressant agent or class. 17 32 34 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only three-quarters of them had a psychiatric condition for which an antidepressant would have been appropriate 30. A more recent study conducted in Italy showed that almost 30% of patients who started an antidepressant drug treatment in 2013 were still on medication 3 years later 31. Among them, 10% used more than 180 defined daily doses (DDDs) per year 31.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only three-quarters of them had a psychiatric condition for which an antidepressant would have been appropriate (30). A more recent study conducted in Italy showed that almost 30% of patients who started an antidepressant drug treatment in 2013 were still on medication three years later (31). Among them, 10% used more than 180 defined daily doses (DDDs) per year (31).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study conducted in Italy showed that almost 30% of patients who started an antidepressant drug treatment in 2013 were still on medication three years later (31). Among them, 10% used more than 180 defined daily doses (DDDs) per year (31). In addition to these significant changes in prescriptions and use over time, the prevalence in antidepressant drug use also varies according to age (12, 14), sex (12), country (14, 25, 32, 33) and antidepressant agent or class (17, 32, 34).…”
Section: Introductionmentioning
confidence: 99%